DISCHOLERETIC AND DYSCHOLEREKINETIC FACTORS AND MECHANISMS OF DEVELOPMENT OF CHOLESTEROL CHOLELITHIASIS - Иванов, Леонид Николаевич; Колотилова, Марина Леонидовна; Алексеева, Наталья Викторовна (Medicine in Kuzbass, 2022)
There are many theories of the genesis of cholelithiasis in the literature, but none of the theories is perfect. Currently, there are no works on the development of experimental prevention of cholesterol cholelithiasis, based on the etiology of cholelithiasis. Based on our theory of the genesis of cholesterol cholelithiasis, we conducted experiments to develop its experimental prevention. These results confirm the correctness of our theory of cholesterol cholelithiasis, and there are also published data supporting this concept. Prevention, from the point of view of the clinic, should be carried out already from the moment of diagnosis of biliary sludge and in the presence of hepatitis of any etiology, chronic acalculous cholecystitis, etc.
Keywords: etiology; cholesterol cholelithiasis; prevention; experimental prophylaxis